Development of Fluorescent Chemosensors for Amino‐Sugars. Issue 3 (19th February 2021) - Yadav, Rohan; Kwamen, Carel; Niemeyer, Jochen
Abstract: In this account, we describe the application of a series of multidentate BINOL‐based phosphoric acids for the fluorescence‐based chemosensing of amino sugars. To this end, we developed a novel synthetic protocol for three isomerically pure phosphoric acid monoesters of the type ArOP(O)(OH)2 . These were investigated with respect to their binding towards amino sugars (glucosamine, galactosamine and mannosamine) in comparison to the previously reported diesters of the type (ArO)2 P(O)(OH). We could find that the diesters show no significant binding, while the monoesters can be used as hosts for amino sugars. Indeed, one host selectively binds to galactosamine, while a second host binds both glucosamine and mannosamine. This allows the fluorescence‐based detection and discrimination of the amino sugars by a novel class of phosphate‐based supramolecular hosts. Abstract :